Attenborough’s echidna rediscovered by combining Indigenous knowledge with camera-trapping - G. Morib; A. Tilker; L.-R Davranoglou; S. D. Anasari; A. Balázs; P. A. Barnes; M. J. Foote; A. Hamidy; C. D. Heatubun; K. M. Helgen; N. Inayah; M. K. Ikhwan; et al. (npj Biodiversity)
Abstract We confirm the ‘rediscovery’ of Attenborough’s long-beaked echidna (Zaglossus attenboroughi), one of only five modern egg-laying mammals and, until now, one of the planet’s most enigmatic ‘lost species’. Unrecorded for 62 years, we present the first scientific evidence of its survival to the present day. We highlight the importance of combining local Indigenous knowledge with camera-trapping to making the rediscovery, and we also discuss follow-up conservation actions to safeguard this Critically Endangered species.